Pengaruh Model Pembelajaran PBL (Problem-Based Learning) Terhadap Pemahaman Konsep Sains pada Materi Gerak dan Gaya di SMPN 25 Kota Bengkulu - Dianasrimurniati Dianasrimurniati; Fadilah Fadilah; Adisel Adisel (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Science education at the junior high school level is often hampered by low conceptual understanding due to the dominance of conventional methods that do not encourage critical thinking. This study aims to determine the effect of the Problem-Based Learning (PBL) model on students' understanding of science concepts, especially on the subject of motion and force at SMPN 25 Bengkulu City. The research method uses a quantitative approach with a quasi-experimental design of the pretest-posttest control group design type. The study population was grade IX students with 30 research subjects in one experimental class (VII B) and a control class (VII C). This study was limited to one school with a relatively small sample size and focused on only one science learning topic. The results of the study from the results of the Independent Sample T-Test hypothesis test value (Sig. 2-tailed) of 0.000 <0.05, which means that H? is rejected and H? is accepted. The results of the analysis show that there is a significant influence between before and after learning using the PBL (problem-based learning) learning model on the understanding of science concepts on the subject of motion and force at SMPN 25 Bengkulu City. This study contributes to the literature on the effectiveness of student-based learning models such as PBL. Different from previous studies that were generally conducted at the high school level or theoretical physics topics, this study provides empirical evidence at the junior high school level with applied science topics, emphasizing the potential of PBL in early science learning. hasil penelitian dari hasil uji hipotesis Independent Sample T-Test nilai (Sig. 2-tailed) sebesar 0,000 < 0,05, yang berarti H? ditolak dan H? diterima. Hasil analisis menunjukkan bahwa terdapat pengaruh yang signifikan antara sebelum dan sesudah pembelajaran menggunakan model pembelajaran pbl (problem-based learning) terhadap pemahaman konsep sains pada materi gerak dan gaya di smpn 25 kota bengkulu. Penelitian ini memberikan kontribusi terhadap literatur tentang efektivitas model pembelajaran berbasis siswa seperti PBL. Berbeda dari penelitian sebelumnya yang umumnya dilakukan di tingkat SMA atau topik fisika teoretis, penelitian ini memberikan bukti empiris di tingkat SMP dengan topik sains terapan, yang menekankan potensi PBL dalam pembelajaran sains sejak dini.